O- and N-glycosides of pyrazolo|3,4-c|isoquinoline. Synthesis and structural investigation by NMR - Bohdan, N.M.; Bohza, S.L.; Bousta, D.; Grafov, A.V.; Holembiovska, O.I.; Khairulin, A.R.; Suikov, S.Yu. (Доповіді НАН України, 2026)
The synthetic potential of polyfunctional derivatives of the condensed system of pyrazolo[3,4-c] isoquinoline has been investigated. For the first time, a series of derivatives with a glucosamine fragment has been obtained and their spectral properties have been described. Досліджено синтетичний потенціал поліфункціональних похідних конденсованої системи піразоло [ 3,4-c] ізохіноліну. Вперше отримано серію похідних з глюкозаміновим фрагментом та описано їхні спектральні властивості .